SLC4A4 compound heterozygous mutations in exon-intron boundary regions presenting with severe proximal renal tubular acidosis and extrarenal symptoms coexisting with Turner's syndrome: a case report - Shoko Horita; Enver Simsek; Tulay Simsek; Nilgun Yildirim; Hiroyuki Ishiura; Motonobu Nakamura; Nobuhiko Satoh; Atsushi Suzuki; Hiroyuki Tsukada; Tomohito Mizuno; George Seki; Shoji Tsuji; et al. (BMC, 2018)
Abstract Background Congenital NBCe1A deficiency with the SLC4A4 mutation causes severe proximal renal tubular acidosis, which often comprises extrarenal symptoms, such as intellectual disability and developmental delay, glaucoma, cataract and band keratopathy. To date, almost all mutations have been found to be homozygous mutations located in exons. Case presentation We performed direct nucleotide sequencing analysis of exons and exon-intron boundary regions of the SLC4A4 in a patient presenting with severe renal proximal tubule acidosis, glaucoma and intellectual disability and her parents without these signs. The examination revealed compound heterozygous mutations in exon-intron boundary regions, c.1076 + 3A > C and c.1772 − 2A > T, neither of which have been reported previously. While the former mutation was found in the mother, the latter was found in the father. The transcript of the SLC4A4 gene was almost undetectable, and the patient was also diagnosed with Turner's syndrome. Conclusions We identified two novel SLC4A4 mutations, c.1076 + 3A > C and c.1772 − 2A > T. When presented in a compound heterozygous state, these mutations caused a phenotype of severe renal proximal tubular acidosis along with glaucoma and mental retardation. This is the first report of congenital proximal renal tubular acidosis carrying compound heterozygous SLC4A4 mutations in exon-intron boundary regions. We suggest that an mRNA surveillance mechanism, nonsense-mediated RNA decay, following aberrant splicing was the reason that the SLC4A4 transcript was almost undetectable in the proband.